Performance of Marketing Assistants in Trisakti School of Tourism - Tri Djoko Sulistio; Lyona Lyona (Journal Hotspot, 2021)
Tourism schools must have a good and structured student acceptance flow. In this activity, it is assessed that the target of prospective students every year will be fulfilled with the help of competent human resources, namely marketing assistant. There are three things affecting each and every marketing assistant such as motivation, work environment, and job performance. This research aims to determine the influence of motivation (X) to work performance (Y) with work environment (Z) as a moderate. The research methods used is quantitative descriptive and the tool is SPSS 24. Data analysis uses simple linear regression analyses and multiple linear regressions with Moderated Regression Analysis (MRA) tests. The samples in this study were marketing assistants of Trisakti School of Tourism, Jakarta. The questionnaire given using random sampling techniques and measured with a questionnaire of 33 statements. The result shows that the work environment is not a moderation variable. It is found out that both motivation and work environment are influential together in determining performance. These results also prove that the working environment is as independent variable in conjunction with performance.